TRANSFORMASI DIGITAL : PEMANFAATAN ARTIFICIAL INTELLIGENCE DAN INOVASI PRODUK LAYANAN UMKM UNTUK MENARIK MINAT PELANGGAN DI ERA DIGITAL - Ageni Trifia; Suci Maghfira Alimuddin; Syahrul Fitra; Mutiara Mutiara; Rahma Nita (Journal of Institution and Sharia Finance, 2024)
This research aims to determine the significant influence of Artificial Intelligence and Product Innovation by linking it to Customer Interest. This research uses a quantitative approach method using data collection techniques by distributing questionnaires and producing a sample of 100 people. Analysis of this research data uses Statistical Product and Service Solutions (SPSS 26). The research results show that Artificial Intelligence does not have a positive and significant influence on Customer Interest. These findings also show that Artificial Intelligence has a significant positive effect on Product Innovation and Product Innovation has a positive effect on Customer Interest for the MSME industry. The findings of this research also show that Customer Interest has a simultaneous influence on Artificial Intelligence and Product Innovation in the scope of Micro, Small and Medium Enterprises.